Politik Hukum Pidana Pengelolaan Eks Dana Program Nasional Pemberdayaan Masyarakat Mandiri Perdesaan (PNPM-MPd) - Aris Tri Wibowo; Abdul Madjid; Rachmi Sulistyarini (Universitas Airlangga, 2021)
AbstractThe management of the former PNPM-MPd funds does not yet have a legal umbrella, both laws, and regulations in other forms. Based on this, the authors see that there are legal problems, namely a legal vacuum (vacuum of Recht) regarding the management of former PNPM-MPd funds so that they have the potential to cause state financial losses (corruption). This paper includes normative juridical research with a statue approach and a conceptual approach. The results showed that the management of former PNPM-MPd funds was not explicitly regulated in statutory regulations. The potential for the occurrence of criminal acts of corruption to be exposed, as evidenced by the existence of criminal acts of corruption regarding the abuse of authority, resulting in losses to state finances. So that it takes legal politics to formulate the management of former PNPM-MPd funds so as not to harm state finances (the occurrence of criminal acts of corruption).Keywords: Political Law; Former Fund of the National Program for Rural Community Empowerment; Criminal Acts of Corruption.AbstrakPengelolaan eks dana PNPM-MPd belum memiliki payung hukum baik undang-undang maupun peraturan dalam bentuk yang lainnya. Berdasarkan hal tersebut, penulis melihat terdapat permasalahan hukum yaitu kekosongan hukum (vacuum of recht) mengenai pengaturan pengelolaan eks dana PNPM-MPd sehingga berpotensi untuk menimbulkan kerugian keuangan negara (tindak pidana korupsi). Makalah ini termasuk penelitian yuridis normatif dengan pendekatan peraturan perundang-undangan (statue approach), dan pendekatan konseptual (conseptual approach). Hasil penelitian menunjukkan bahwa pengelolaan eks dana PNPM-MPd tidak diatur secara eksplisit di dalam peraturan perundang-undangan. Potensi terjadinya tindak pidana korupsi menjadi terbuka, terbukti dengan adanya tindak pidana korupsi mengenai penyalahgunaan kewenangan sehingga menimbulkan kerugian keuangan negara. Sehingga diperlukan politik hukum untuk melakukan formulasi pengelolaan eks dana PNPM-MPd agar tidak merugikan keuangan negara (terjadinya tindak pidana korupsi).Kata Kunci: Politik hukum; Eks Dana Program Nasional Pemberdayaan Masyarakat Perdesaan; Tindak Pidana Korupsi.